Coordination of Rad1–Rad10 interactions with Msh2–Msh3, Saw1 and RPA is essential for functional 3′ non-homologous tail removal - Eichmiller, Robin (Nucleic Acids Res, 2018)
Double strand DNA break repair (DSBR) comprises multiple pathways. A subset of DSBR pathways, including single strand annealing, involve intermediates with 3′ non-homologous tails that must be removed to complete repair. In Saccharomyces cerevisiae, Rad1–Rad10 is the structure-specific endonuclease that cleaves the tails in 3′ non-homologous tail removal (3′ NHTR). Rad1–Rad10 is also an essential component of the nucleotide excision repair (NER) pathway. In both cases, Rad1–Rad10 requires protein partners for recruitment to the relevant DNA intermediate. Msh2–Msh3 and Saw1 recruit Rad1–Rad10 in 3′ NHTR; Rad14 recruits Rad1–Rad10 in NER. We created two rad1 separation-of-function alleles, rad1R203A,K205A and rad1R218A; both are defective in 3′ NHTR but functional in NER. In vitro, rad1R203A,K205A was impaired at multiple steps in 3′ NHTR. The rad1R218A in vivo phenotype resembles that of msh2- or msh3-deleted cells; recruitment of rad1R218A–Rad10 to recombination intermediates is defective. Interactions among rad1R218A–Rad10 and Msh2–Msh3 and Saw1 are altered and rad1R218A–Rad10 interactions with RPA are compromised. We propose a model in which Rad1–Rad10 is recruited and positioned at the recombination intermediate through interactions, between Saw1 and DNA, Rad1–Rad10 and Msh2–Msh3, Saw1 and Msh2–Msh3 and Rad1–Rad10 and RPA. When any of these interactions is altered, 3′ NHTR is impaired.